Classification of agarwood oil using an electronic nose - Wahyu, Hidayat; Ali Yeon, Md Shakaff, Prof. Dr.; Mohd Noor, Ahmad, Assoc. Prof. Dr.; Abdul Hamid, Adom, Assoc. Prof. Dr. (MDPI Publishing, 2010)
Link to publisher's homepage at http://www.mdpi.com/